Anionic hafnium species: an active catalytic intermediate for the coupling of epoxides with CO2?. Issue 50 (5th June 2019) - Lalrempuia, Ralte; Underhaug, Jarl; Törnroos, Karl W.; Le Roux, Erwan
Abstract : A series of hafnium complexes were structurally identified showing high activity (up to 500 h −1 ) in the selective alternated copolymerization of epoxides with CO2 under low pressure. Abstract : A series of hafnium complexes were structurally identified showing high activity (up to 500 h −1 ) in the selective alternated copolymerization of epoxides with CO2 under low pressure.